1996
DOI: 10.1073/pnas.93.24.13819
|View full text |Cite
|
Sign up to set email alerts
|

Multiple A-type cyclins express sequentially during the cell cycle in Nicotiana tabacum  BY2 cells

Abstract: Four full-length and one partial cDNA clones encoding four different A-type cyclins were isolated from a tobacco S-phase-specific library. The corresponding mRNAs displayed sequential appearance and disappearance during the cell cycle of highly synchronized suspension-cultured tobacco cells. Sequence analysis showed that the plant A-type cyclins can be subdivided into three distinct structural groups that are likely to be represented in every plant species. Two of the isolated tobacco cyclins belonging to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 27 publications
10
100
0
Order By: Relevance
“…In Arabidopsis, there are two A1 (CYCA1;1 and CYCA1;2) and four A2 and A3 (CYCA2;1 to CYCA2;4 and CYCA3;1 to CYCA3;4) genes (Chaubet-Gigot, 2000;Vandepoele et al, 2002), and maize A-type cyclins are likely to show similar complexity. Different Arabidopsis A-type cyclins were reported to be expressed sequentially at different time points from late G1/early S-phase until mid-M-phase (Reichheld et al, 1996). Consequently, it is possible the maize A1;3-type cyclin/CDK functions during S-phase and/or the G2/M transition, as was suggested for the Medicago sativa A2-type cyclin-associated CDK (Roudier et al, 2000).…”
Section: Zeama;krps Are Ckis That Can Affect Cyclin A/cdk and Cyclin mentioning
confidence: 98%
“…In Arabidopsis, there are two A1 (CYCA1;1 and CYCA1;2) and four A2 and A3 (CYCA2;1 to CYCA2;4 and CYCA3;1 to CYCA3;4) genes (Chaubet-Gigot, 2000;Vandepoele et al, 2002), and maize A-type cyclins are likely to show similar complexity. Different Arabidopsis A-type cyclins were reported to be expressed sequentially at different time points from late G1/early S-phase until mid-M-phase (Reichheld et al, 1996). Consequently, it is possible the maize A1;3-type cyclin/CDK functions during S-phase and/or the G2/M transition, as was suggested for the Medicago sativa A2-type cyclin-associated CDK (Roudier et al, 2000).…”
Section: Zeama;krps Are Ckis That Can Affect Cyclin A/cdk and Cyclin mentioning
confidence: 98%
“…Expression of PCNA and A3-type cyclin genes starts at the G1 phase and their expression levels reach a maximum in S phase (Reichheld et al 1996;Sekine et al 1999;Jang et al 2005); thus, we chose these two genes as markers of the G1-S transition. The accumulation of gene transcripts in control cells started at 4-6 h (PCNA) or at 6-8 h (Nicta;CycA3;3), and reached their expression peak at 10 h, when several cells entered S phase ( Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results indicating that the levels of DNA synthesis and gene expression are uncoupled were also reported in A3-type cyclins. Reichheld et al (1995Reichheld et al ( , 1996 reported that the expression of NtcycA59 and NtcycA105 (renamed Nicta;CycA3;1 and Nicta;CycA3;2, respectively; reviewed by Hemerly et al 1999) was not N. Suda et al suppressed by the addition of aphidicolin to tobacco BY-2 cells in the stationary phase, even though DNA synthesis rates decreased. This suggests that the expression level of A3-type cyclin genes and the level of DNA synthesis are not always correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, most key regulators of the (supposedly more distant) animal cell cycle seem to be conserved in higher plants. The occurrence of cyclins and cyclin-dependent protein kinases in higher plants similar to those found in animals is now well established (Ferreira et al, 1991(Ferreira et al, , 1994Hemerly et al, 1992 ;Reichheld et al, 1995Reichheld et al, , 1996, and retinoblastoma protein homologues (Murray, 1997 ;Murray et al, 1997 ;Huntley et al, 1997) and cdc25 homologues (Sabelli et al, 1998) have been isolated recently. Given this overall conservation of cell cycle machinery and circumstantial evidence such as the fact that in a number of cyclins the primary structure reveals signatures for post-translational modifications dependent on cAMP (analogous to cyclin D " ), the observation made by Ehsan et al (1998) demands a further search for a role for cAMP in the plant cell cycle.…”
Section:    C mentioning
confidence: 94%